GAYA BELAJAR SISWA BERPRESTASI PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI 03 CIBELOK PEMALANG - Kusumawati Kusumawati.; Diana Endah H; Singgih Adhi P (Universitas Syiah Kuala, 2018)
This study aimed to identify students’ learning styles in learning Mathematics. This research is a qualitative research. The research participants were fifth grade students of public elementary schools 03 Cibelok Pemalang which consisted of 5 people. The methods of data collection used were questionnaires, interviews, observations, and documentation. Data collected were analyzed using descriptive analysis. The results of the study on class V students public elementary schools 03 Cibelok Pemalang regency showed that achievement students 'learning styles in learning Mathematics dominant learning style of the students are visual with the distribution of values that is 846.